2014
DOI: 10.17511/ijmrr.2014.i04.14
|View full text |Cite
|
Sign up to set email alerts
|

Study of Etiological factors, mycological profile and treatment of Otomycosis

Abstract: Introduction: Otomycosis is a common condition encountered in ENT practice. Though it is not a serious condition it causes a lot of misery to the patient. Though there are many studies on various aspects about this disease, there are not many studies from this part of the country. Materials and Methods: 75 patients attending ENT OPD and diagnosed to have otomycosis were included in the study. Two aural swabs or whenever possible otomycotic debris scooped out using Jobson-Horne probe was obtained. From one swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Bacterial infection of auditory canal may be one of the predisposing factors for development of otomycosis [5]. Mixed bacterial and fungal infections were also reported in a studies carried out in Indian [29,26,30].…”
Section: Discussionmentioning
confidence: 86%
“…Bacterial infection of auditory canal may be one of the predisposing factors for development of otomycosis [5]. Mixed bacterial and fungal infections were also reported in a studies carried out in Indian [29,26,30].…”
Section: Discussionmentioning
confidence: 86%
“…(3,(22)(23)(24) A study reported that the awareness regarding unnecessary usage of cotton bud is much effective to prevent otomycosis. (25) Another study on hazards of ear buds revealed that peoples use ear buds to remove ear wax or to absorb fluid discharging from ear canal, as they are not aware of numerous pathologies which are curable risk factors regarding with frequent use of ear buds. Moreover, they stated that awareness should be created among general population as it can cause deafness and other infections (26).…”
Section: Discussionmentioning
confidence: 99%
“…It is usually associated with increased ear canal moisture, warmth and use of topical antibiotic ear drops, which may lead to depletion of protective cerumen layer, maceration of underlying skin, increase in ambient pH and modification of the microbial flora of external auditory canal. Many studies have been revealed that itching in the ear and earache are the major clinical feature of otomycosis [14][15][16][17][18][19][20][21] . However, in this case study, both patients had many clinical features viz; earache, heaviness, ear blockage and ear discharge.…”
Section: Discussionmentioning
confidence: 99%